A scoping review to examine health care professionals’ experiences as family caregivers - Kristina M. Kokorelias; Nira Rittenberg; Orianna Scali; Suzanne Smith-Bayley; Monique A. M. Gignac; Gary Naglie; Jessica Sheirs; Jill I. Cameron (PLoS ONE, 2025)
Background Health and social care systems must confront the challenge of supporting a growing elderly population and their caregivers. Family caregivers who are healthcare professionals are part of this context, but their caregiving experiences remain unclear. Objective This scoping review explored the experiences of healthcare professionals who are also family caregivers for older adults. Methodology A scoping review methodology identified and summarized pertinent studies. Searches were conducted in Medline, Embase, PsycINFO, CINAHL, and AgeLine. We sought articles published from each journals’ inception to October 19, 2023. Inclusion criteria were English-language studies about healthcare professionals caring for older adult family members. Diverse research designs were included. Data were extracted and synthesized according to key themes. Results The review included 19 studies, highlighting four themes. Studies were published between 1994 and 2019, with most studies published before 2017. The overarching theme was "Expectations," where healthcare professional family caregivers faced multifaceted expectations from themselves, their families, and the healthcare system. Expectations also highlights the dual role of participants as both caregivers and healthcare professionals This complex interplay led to a theme related to personal consequences, including stress, guilt, and potential burnout, but also positive aspects of the dual roles. Studies described how dual roles could enhance the quality-of-care healthcare professional caregivers provided to their family members. Finally, support needs were identified, emphasizing the importance of workplace accommodations and support from the healthcare system and peers. Conclusions The experiences of healthcare professional family caregivers are shaped by unique expectations, resulting in both positive and negative consequences. The support needs of this group are multifaceted, requiring workplace accommodations and tailored support within the healthcare system. Further research is needed to delve deeper into the nuances of their experiences and develop targeted interventions to alleviate the stress and challenges they face in their dual roles. Understanding the evolving needs of healthcare professional family caregivers over time can inform support strategies along the caregiving trajectory.